Draft Annual Plan 1986-87 Volume : VI Government of Assam - Planning Commission (Planning Commission, 1986)
India is a signatory to Alma Ata declaration committing to attaining the goal of %Health for all by the year 2000A.D." and is proposed to achieve the goal through primary Health Care approach by providing universal Comprehensive primary Health care service relevant to the actual need and priority of the Community, at a cost which people can afford and through active participation of the community.
Government of Assam, Planning and Development Department